Penggunaan Media Puzzle dalam Memotivasi Belajar Siswa Kelas III SD Negeri 126 /II Tanjung Agung - Diah Febianti; Marsya Deva Azilla; Syahrial Syahrial; Silvina Noviyanti (AS-SABIQUN, 2022)
The use of puzzle media can increase students' learning motivation. With this puzzle media, students are more enthusiastic to learn in class. This research was conducted in the third grade of SD Negeri126 /II Tanjung Agung This study aims (1) to describe how the use of puzzle media in motivating student learning, (2) to describe the obstacles faced by teachers in using puzzle media to motivate student learning in Theme 6 subtheme 2 Learning 2nd grade III SD Negeri 126 /II Tanjung Agung. The research subjects were all thirdgrade students of SD Negeri 126 /II Tanjung Agung, totaling 32 students, 13 male students and 19 female students. The data obtained were then processed using qualitative methods with descriptive research types. So that the results can be seen from the learning motivation of each student. Data collection in this study was carried out using observation and interviews, then the data was narrated. From a series of research processes carried out and the results of observations indicate that the teacher provides direction or encouragement to students during the teaching and learning process. The teacher also gives praise and gifts to students who are active in the class. Based on the results of the interviews, it was found that the teacher did not experience problems during the puzzle preparation process carried out by students, because students were very excited when preparing puzzles and the class atmosphere became active so that students were very motivated by the teacher using this puzzle media when the teaching and learning process took place in the classroom. There are some students who have not been motivated by using puzzle media in the teaching and learning process in this lesson, so that the teaching and learning process runs smoothly because students who are not motivated do not disturb their friends who are studying.